ISTILAH KOSA KATA KULINER BALI - I MADE SUWETA (Purwadita : Jurnal Agama dan Budaya, 2018)
When associated with the language system, the knowledge of the Balinese culinary term is a vocabulary of Balinese traditional cuisine. The terms and vocabulary in the culinary field of Bali are very diverse. Seen from the structure of the language and the structure of word formation, many still do not understand the origin of the formation of these terms because each word and terms have a language structure. In this study the theory used is structural theory, which was originally used by Ferdinand de Saussure in his book de Linguistique Generale. In the study also use the method of observation and refer to literature review (in the discovery of data), while in the exposure used qualitative method with a combination of inductive and deductive techniques. Based on research and discussion, it can be concluded that the terms of culinary Bali is very diverse and many types. In addition, based on the data of culinary terms Bali, found the Balinese language vocabulary Bali culinary terms that are formed through the affixation process, both prefix, infix, suffix, and confix. Thus, it can be said that the term culinary Bali through the affixation process found in many prefixes, suffixes, and confiks, whereas in the infix did not find any culinary terms Bali.